Conformal field theory, automorphic forms and related topics: CFT, Heidelberg, September 19-23, 2011 - Kohnen, Winfried; Weissauer, Rainer (Contributions in mathematical and computational sciences, 2014)
1. A. Milas: Characters of Modules of Irrational Vertex Algebras -- 2. G. Mason: Lattice subalgebras of strongly regular vertex operator algebras -- 3. C. Dong and C. Jiang: A Characterization of the vertex operator algebra V -- 4. H. Yamauchi: Extended Griess algebras and Matsuo-Norton trace formulae -- 5. M.R. Gaberdiel and R. Volpato: Mathieu Moonshine and Orbifold K3s -- 6. M.C.N. Cheng and J.F.R. Duncan: Rademacher Sums and Rademacher Series -- 7. G. Mason and M.P. Tuite: Free Bosonic Vertex Operator Algebras on Genus Two Riemann Surfaces II -- 8. A. Zuevsky: Twisted correlation functions on self-sewn Riemann surfaces via generalized vertex algebra of intertwiners -- 9. T. Gannon: The theory of vector-valued modular forms for the modular group -- 10. A.I. Molev and E.E. Mukhin: Yangian characters and classical W-algebras -- 11. Appendix: G. Mason: Vertex Operator Algebras, Modular Forms and Moonshine
Description based upon print version of record
Keywords: Konferenzschrift -- 2011 -- Heidelberg; Automorphe Form; Konforme Feldtheorie; Vertexalgebra